Scoping Review on Knowledge, Attitudes, and Practices of Safety Promotion in Academic Laboratories - Turmaningsih Surya Pratama; Bagoes Widjanarko; Daru Lestantyo; Yuliani Setyaningsih (Postgraduate, University of Mataram, 2025)
This scoping review aims to invistigate safety promotion within academic laboratory environments, with a specific emphasis on culinary academic laboratories. The review aims to detect trends in literature, evaluate safety promotion approaches, and analyze their effects on participants' Knowledge, Attitudes, and Practices (KAP). The evaluation complied with PRISMA-ScR criteria, utilizing Scopus as the principal database, encompassing peer-reviewed articles published from 2014 to 2024. A total of 23 pertinent studies were included following the application of eligibility criteria. The research found twelve unique strategies of safety promotion, encompassing sustainable practices, ergonomic scheduling, health education, and community involvement. The results were classified into KAP outcomes, with several studies indicating enhanced safety knowledge, improved attitudes toward safety procedures, and favorable practical safety results. Notwithstanding the proliferation of literature on safety promotion, considerable deficiencies persist, especially with the distinct hazards present in culinary university laboratories. The evaluation determines that more research is necessary to fill these gaps and establish appropriate safety standards specific to culinary teaching environments.